Abundancia y distribución vertical de la meiofauna en la playa fangosa de Punta Morales, Golfo de Nicoya, Costa Rica - Cruz, Elba de la (1987)
The abundance and vertical distribution of meiofauna on a tropical (10°N) intertidal mud flat (more than 30% silt + clay) were evaluated from February through September of 1984. Six core samples (core area: 5.3 cm2) were collected monthly to a depth of 6 cm into the sediment, and preserved in a solution of formalin in sea water stained with Rose Bengal. Organisms within a size range of 63 to 500 microns were considered as meiofauna.We collected a total of 16 taxonomic groups represented by 48,411 individuals. Nematoda, Foraminifera, Ostracoda, and Copepoda (Harpacticoida) comprised 88.1%, 5.9%, 2.9%, and 1.1 % of the total, respectively. Density and faunal composition were similar to those reported from other intertidal environments. Density ranged from 1.17 to 4.25 x 106 ind. /m2 (mean = 2.17).Most of the meiofauna was restricted to the top 2 cm of the sediment. This distribution is probably related to the existence of a shallow (less than 2 cm deep) brown aerobic layer in the sediment.